Attitude of Agricultural Beneficiaries towards NGOs in North Coastal Andhra Pradesh - Chitrasena Padhy, Chitrasena Padhy; Akhila Badavath, Akhila Badavat; Atanu Deb, Atanu Deb; Bikramjeet Ghose, Bikramjeet Ghose (Indian Journal of Extension Education, 2025)
Non-government organisations play a vital role in meeting societal needs. The study, conducted in 2025, explores the influence of socio-economic factors on attitudes of beneficiaries towards NGOs engaged in agricultural development and poverty alleviation. The purpose of this study was to evaluate beneficiaries’ attitudes toward NGOs in the districts of Vizianagaram and Srikakulam in Andhra Pradesh’s North Coastal regions. A purposive sampling design was used for the selection of districts. Two NGOs from each district were selected based on their performance. 15% of the beneficiaries from each NGO were randomly selected from each district, resulting in a total of 90 farmers. So, in total, 180 farmers were selected from both districts. The analysis of variance (ANOVA) revealed that attitude scores significantly differed by education, age, income, and land holding size (p<0.01). The multiple regression analysis revealed that scientific orientation, health security, and housing conditions emerged as significant predictors. Respondents with basic education and those below 50 years of age showed more significant attitudes than illiterate, graduate, and older individuals. Random forest analysis revealed that scientific orientation, health security, family support, and social participation were key contributors.